Variation of Clinical Estimation of Foetal Weight: Experience of 247 Cases in Dhaka City - Firdousi, Tahmida; Begum, Taslima; Akter, Shimul; Mohammad, Nur (Journal of Science Foundation, 2019)
Background: Foetal weight detection can vary by examining clinically. Objective: The purpose of the present study was to see the variation of clinical foetal weight among the newborn infant. Methodology: This prospective cohort study was carried out in the Department of Obstetrics & Gynaecology at Rajshahi Medical Hospital, Rajshahi, Bangladesh from July 2012 to June 2014 for a period of 2(two) years. Pregnant women with known gestational age at term (38 to 40 weeks of pregnancy), singleton pregnancy with longitudinal lie were included in this study. The clinical estimation of foetal weight was done. Actual birth weights of babies were measured soon after their birth. This weight was measured within the first hour of life. They were weighed naked. Result: A total number of 245 pregnant women in term pregnancy were recruited as per inclusion and exclusion criteria. Majority of the women [91(37.1%)] belonged to the age group 25 to 29 years, 83 (33.9%) in the age group 19 to 24 years. Low Birth Weight was found 14(5.7%) cases in clinical examination and 15(6.0%) cases in actual cases. Normal birth weight was found 215(87.8%) cases and 221(90.3%) cases in clinical examination and actual weight respectively. The mean with SD of foetal weight among the study population were 3283.27±461.05 gm and 2936.20±456.71 gram in clinical examination and actual weight respectively (p < 0.05). Conclusion: In conclusion there is a significant variation of clinical estimation of foetal weight Journal of Science Foundation 2018;16(2):60-64